Association of Knowledge and Practice of Home Blood Pressure Monitoring (HBPM) Among Second-Year Medical Students - Rashid, Aneesa Abdul; Thew, Hui Zhu; Zakaria, Zulaikha; Mohd Faizal, Muhammad Shafirul Daniel; Cheng, Choo Zhi (International Journal of Human and Health Sciences (IJHHS), 2024)
Objective: Hypertension is a global public health challenge, often exhibiting suboptimal management resulting in numerous health complications. Home blood pressure monitoring (HBPM) is a valuable tool for aiding healthcare providers in the diagnosis and treatment of hypertension in patients. Approximately 15% of individuals with hypertension fall within the young adult demographic, ranging from 18 to 39 years old. The early onset of hypertension exposes them to a heightened risk of cardiovascular events occurring prematurely. Consequently, the objective of this research is to assess the association of knowledge of HBPM with practice among medical students. Methods: This was part of a larger study entitled: “Effect of Video Intervention on Knowledge of Proper Home Blood Pressure Monitoring Among Second Year Medical Students, UPM”. It was a cross sectional study done among all second-year medical students in the Universiti Putra Malaysia from April 2022 to 2023 (JKEUPM-2022-143). The students were given online questionnaires on HBPM. The questionnaire underwent content validation by a panel of experts. It consisted of 20 questions on knowledge, with one point for each correct answer. A higher score indicates better knowledge. There were two questions on practice which asked if they did HBPM on themselves or their family members/friends. Results: We report (n=21, 24.1%) of participants do their blood pressure at home, while (n=45,51.7%) do BP monitoring at home to their family members/friends. The mean (+sd) knowledge scores out of a possible 20 for these groups are 10.81 (+ 3.0) and 11.29 (+2.5) respectively. Those who assisted family members/friends with their BP at home had significantly more knowledge scores that those who didn’t (mean difference= 2.7, p=0.000). No significant associations with the group with self BP monitoring. Conclusion: Therefore, we conclude that those who assist others in HBPM have significantly higher knowledge scores compared to those who did not. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S50